Flexural and compressive behaviour of composite concrete reinforced with 1.0% of polyester / Azizan Zainal (Faculty of Civil Engineering, 2003)
Nowadays, it has been found that high strength concrete (HSC) is applicable for high-rise construction or multy-storey building. In Malaysia, Kuala Lumpur Twin Tower or KLCC was used HSC at grade 80 MPa for columns and ring beams on the lower floor of towers. Silica fume also was employed as cement replacement of HSC for the construction of KLCC to increase compressive strength of concrete. However, high strength silica fumes concrete without reinforcement is still a brittle material which has low tensile strength and strain capacities, weak to resist against crack propagation, impact, creep, fracture toughness and also has low ductility. The combination of SF (as cement replacement) and polyester (PL) fiber (as admixture material) in HSC will enhanced and improved the mechanical properties of HSC. This research is an experimental investigation on the compressive and flexural behaviour of 60 MPa HSC due to 12% and 16% SF (as cement replacement) and 1.0% PL fiber (as admixture material) at 0.35 water cement ratio. Plain concrete is used as control specimen done by Ramli Ishak (2003). The present of 1% PL with 12%SF caused an increase in compressive strength, however 1% PL with 16% SF caused a slight decrease in compressive strength. The present of 1% PL also increased the flexural strength. Fiber also controlled crack propagation and acted as tensile reinforcement.